Trajectories of Vulnerability of Rural Territories in the Ecuadorian Andes: a Comparative Analysis - Nasser Rebaï; Julio A. Alvarado Vélez (Revue de Géographie Alpine)
While the peasant populations of the Ecuadorian Sierra have been marked by multiple constraints in their history, for thirty years, the liberal policies that aimed at the “modernization” of the primary sector of the economy in Ecuador have led to profound changes in the Andean regions. From fieldwork conducted in the provinces of Azuay, Cotopaxi and Chimborazo, during which interviews with institutional actors and surveys within family farms were carried out, it was highlighted that the disappearance of public agricultural services, the promotion of chemical pesticides and the development of mining have favored the disunity of the peasant groups. In addition, we observed that in recent years, family farmers have developed agricultural practices that have adverse effects on the environment while, at the same time, their food security was not ensured. Finally, the work done over the past three years provides an opportunity to take stock of the negative effects of the “modernizing” project of the primary sector in Ecuador and, through the comparison of several local situations, to characterize the extension of the trajectory of vulnerability of Andean rural territories.